O DIAGNÓSTICO COMO INSTRUMENTO ESTRATÉGICO PARA A VALORAÇÃO DA COMUNICAÇÃO ORGANIZACIONAL: Teorias e Práticas - GAVIOLLI, FABIANA MOREIRA (2017)
This dissertation addresses the use of diagnosis as an instrument that if it is used strategically can provide conditions for organizational communication to create value. The diagnosis is the foundation of planning by establishing priorities, support the formulation of strategies and point out discrepancies between perceptions of the real world scenario and the projected scenario. This research is bibliographical and contains semi-structured interviews with organizational communication agencies that offer the diagnosis on their own services menu as a way to align concepts and practices of the diagnosis in organizational communication. The main goal is to investigate how the diagnosis may contribute to the valuation of organizational communication for organizations. At the end of this study, we present a suggestion of Public Relations Diagnostic Model for Organizational Communication and through this model, we show how to reflect the contrast found between theory and practice of diagnosis in Organizational Communication. The considerations presents a prognosis, as a result of this study as a diagnosis and it is a warning for that the relationship between the academy and the market that could be greater and better. From this behaviour, we would be able to foresee the future of strategic organizational communication leaving a speech and become practical reality in the organizations.